EFFECT OF AUDITOR INDUSTRY EXPERTISE ON AUDITOR’S LIABILITY OF LISTED FINANCIAL FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
This study examined the effect of audit industry expertise on auditor’s liability of listed financial firms in Nigeria. It has become  quite worrisome that investors are finding somewhat difficult to make reliable and informed financial decisions that will have positive impact on businesses due to the apparent lack of audit quality. Specifically, the study seeks to determine the effect of audit fees, audit firm size and auditor’s tenure on audit litigation. The study relied on secondary data source, which extract from the 2012 – 2022 financial statements of 49 financial firms listed on the Nigerian Exchange Group as at 31st December, 2022, were further exposed to statistical analysis using the OLS multiple regression with the aid of E- View 10 output statistical software. Findings obtained showed that audit fees and larger audit firm size were significantly associated with a lower likelihood of audit-related litigation, while auditor's tenure was not found to have a significant effect on audit-related litigation. It was therefore recommended that audit firms should increase its audit fees, even stakeholders should consider the audit firm size when evaluating the financial statements of firms and better reputation which can help to reduce the likelihood of audit-related litigation. Moreso, auditing firms should focus on other factors such as the quality of the auditor's work and the reputation of the audit firm, when assessing audit quality. With these, auditing practices can become consistent and effective, regardless of expertise and/or the length of time an auditor has been with a particular firm
Keywords: Audit Fees; Audit Quality; Audit Industry Expertise; Audit Litigation; Audit Tenure